Potensi E-Student Worksheet Terintegrasi Danau Tondano Sulawesi Utara dalam Meningkatkan Kognitif Siswa SMA: Analisis Kebutuhan - Crescentia Mishi Juniorita Ngangi; Paidi; Emma Mauren Moko; Jantje Ngangi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the needs of teachers and students for the development of teaching materials based on local issues in environmental change topics in senior high school biology learning. The method used was a descriptive study with a preliminary study approach through needs analysis. Data were collected through interviews and questionnaires administered to teachers and students of senior high schools in Tondano, North Sulawesi. The results show that environmental change learning materials are still commonly presented using general contexts that have been repeatedly used, such as global warming, and have not optimally utilized the surrounding environment as a learning resource. Teachers expressed the need for teaching materials in the form of an E-Student Worksheet based on local issues and integrated with technology to increase students’ learning interest. Students also responded positively to the development of open learning activities that incorporate local environmental issues and utilize technology. In conclusion, the development of an E-Student Worksheet based on environmental changes in Lake Tondano is necessary to support contextual learning and improve students’ cognitive competence through the use of technology. Keywords: Needs Analysis, Danau Tondano, E-Student Worksheet